Predictors of time to first birth after first marriage among women in Uganda - Mubiru, Frank; Atuhaire, Leornard K.; Lubaale, Yovani Moses; Wamala, Robert (African Population Studies, 2016)
The objective of this paper was to investigate factors associated with time to first birth after first marriage among women in Uganda. The assessment was made using data sourced from the 2011 Uganda Demographic and Health survey. The analysis was done using a time-to-event approach involving life tables, log-rank and the Cox Proportional Hazards model. In the results, the median time to first birth after first marriage was 2 years (range, 1-36). The key predictors of having a live birth after first marriage were loss of a pregnancy either spontaneously or induced, knowledge of ovulation cycle and late sexual debut (p < 0.05). In particular, the chances of first birth after first marriage were lower among women who had ever lost a pregnancy and women having their sexual intercourse at a later age. On the contrary, the chances of having a first child after marriage were higher among women at higher ages at first marriage and those who were aware of their ovulation cycle.
Keywords: First marriage; Time to first birth; Uganda